Outlook for the Use of Neurodevelopmental Therapy in Children with Perinatal Central Nervous System Damage: a Review - Maya A. Khan; Elena V. Kostenko; Natalya A. Mikitchenko; Maria G. Degtyareva; Zareta Kh. Shungarova (Вестник восстановительной медицины)
INTRODUCTION. The significant incidence of perinatal damage to the central nervous system (CNS) and the high risk of its adverse outcomes determine the relevance of medical rehabilitation of such children. Kinesiotherapy methods, being the most physiological and gentle, take a leading place in the system of rehabilitation measures for patients with perinatal damage to the CNS. In recent years, there has been renewed interest in the use of Bobath neurodevelopmental therapy, aimed at correcting pathological motor stereotypes and the formation of age-related motor skills through sensory stimulation of proprioception.